The classroom : when nature calls, hang up! - Mellom, Robin (Mellom, Robin. Classroom, 2015)
The school year is almost over and it is time for Westside Middle School's annual camping trip, something that Trevor Jones would desperately like to get out of as he is terrified at the prospect of coyotes, bears, dining halls, and eighth graders--and his cabin is supposed to be haunted.